Peran Media Pembelajaran dalam Meningkatkan Keterampilan Gerak Dasar dalam Menembak Bola Basket - Jamaludin Bahtiar Gui (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2025)
Media is very important For learning. For success learning, creativity a educators are very important. If the media is adjusted with wisdom local, results Study student will increased. Purpose of writing article This is For explain the role of media in increase results Study students. For do writing This, review method is used For analyze published references​ online related​ with learning media. In addition, the impact positive from reference the to results learning is also evaluated. The results of the analysis show that study about the influence of learning media to results learning basketball is very significant. Various branch sport has developing motion media base for basketball. This is a lot done with using interactive media Because progress technology information. How do educators use wisdom local For changing media also has a big influence to results Study basketball motion.